Pengaruh Fintech dan Literasi Keuangan terhadap Kinerja UMKM dengan Peran Moderasi Digital Marketing - Budi Gautama Siregar; Muhammad Salman Salman; Aswadi Lubis (Jurnal Penelitian Ekonomi Akuntansi, 2026)
This study aims to analyze the effect of financial technology, financial literacy, and digital marketing on the performance of MSMEs in Padangsidimpuan City using the Technology Acceptance Model approach. The research employs a quantitative method with Structural Equation Modeling based on Partial Least Square (SEM-PLS) as the analytical technique. The results indicate that financial technology has a positive and significant effect on MSME performance, although its contribution is relatively moderate. Meanwhile, financial literacy is found to be the most dominant variable in improving business performance, as strong financial management capabilities lead to more effective decision-making. Digital marketing also has a positive impact on MSME performance and acts as a moderating variable that strengthens the relationship between fintech, financial literacy, and business performance. Overall, the findings reveal that MSME performance is influenced not only by technology adoption but also by human resource capacity and digital marketing strategies. Therefore, synergy among fintech utilization, financial literacy enhancement, and digital marketing optimization is essential. The limitation of this study lies in its limited geographical scope and reliance on perception-based data. Future research is recommended to expand the study area and incorporate additional variables for more comprehensive results.